Status of ratification of Agreement negotiated under the auspices of the Arctic Council. - Arctic Council (Arctic Council Secretariat, 2015)
Status of ratification of Agreements negotiated under the auspices of the Arctic Council, submitted to the Arctic Council's Senior Arctic Officials meeting in Whitehorse, Canada, March 4-5 2015.